The Analysis Of The Role Of Traditional Bugis Cuisine In Attracting Tourists In Sidenreng Rappang Regency - Andika Andika; Yusrianti Yusrianti; Yayuk Astuti; Damayanti Trisnasari (Universitas Negeri Padang, 2025)
This study examines the contribution of traditional Bugis cuisine in attracting tourists to Sidenreng Rappang Regency and tourists' perspectives on the local cuisine. Using a descriptive qualitative approach, data ware collected through in-depth interviews, participatory observation, and documentation at three traditional culinary locations: Roti Beras Hj. Mako, Bolu Cukke Diana, and Bebek Palekko Gazebo, With one informant as the owner, two employees, and one customer at each location. Data analysis was conducted using NVivo software to identify key themes related to culinary tourism appeal. The findings indicate that Bugis cuisine, such as Palekko, Bolu Cukke, and Roti Beras, have significant potential as a tourist attraction due to its distinctive taste, use of local ingredients, and traditional cooking techniques that are preserved. However, the management of this cuisine is still hindered by limited promotion and accessibility. This study recommends enhancing promotion through social media and organizing cultural events to introduce Bugis cuisine to a wider audience. Collaboration between local governments and culinary entrepreneurs is also crucial for developing traditional cuisine as a sustainable tourism product. The contribution of this study lies in providing new insights into the role of traditional cuisine in cultural-based tourism development and offering practical recommendations for the sustainable development of culinary tourism.